Formation and effect of lanthanum based-anodic coating on corrosion resistance of AZ31 magnesium alloy - Mohd Zahiruddin, Md. Zain; Takenake, Toshihide; Norshah Afizi, Shuaib; Mokhtar, Mat Saleh; Azmi, Harun (Universiti Malaysia Perlis (UniMAP), 2011)
Organized by Universiti Malaysia Perlis (UniMAP) and Malaysian Solid State Science & Technology Society (MASS), 21st - 23rd December 2009 at Bayview Beach Resort, Ferringhi in the Pearl of the Orient, Penang, Malaysia.